Minimizing path loss and improving security in wireless body area networks. Issue 1 (2nd March 2021) - Anguraj, Dinesh Kumar; Bashar, Abul; Nidhya, R.; Shimna, P.K.; Ravi, Renjith V.
Abstract : Purpose: The purpose of this paper is energy consumption and security. To extend the sensor's life span, saving the energy in a sensor is important. In this paper, biosensors are implanted or suited on the human body, and then, transposition has been applied for biosensors for reducing the sensor distance from the sink node. After transposition path loss has been calculated, security is maintained and also compared the results with the existing strategies. Design/methodology/approach: Nowadays, one of the most emergent technologies is wireless body area network (WBAN), which represents to improve the quality of life and also allow for monitoring the remote patient and other health-care applications. Traffic routing plays a main role together with the relay nodes, which is used to collect the biosensor's information and send it towards the sink. Findings: To calculate the distance and observe the position, Euclidean distance technique is used. Path loss is the main parameter, which is needed to reduce for making better data transmission and to make the network stability. Routing protocols can be designed, with the help of proposed values of sensors locations in the human body, which gives good stability of network and lifetime. It helps to achieve as the less deplete energy. Originality/value: This scheme is compared with the two existing schemes and shows the result in terms of parameter path loss. Moreover, this paper evaluated a new method for improving the security in WBAN. The main goal of this research is to find the optimal sensor location on the body and select the biosensor positions where they can get less energy while transmitting the data to the sink node, increasing the life span in biosensors, decreasing memory space, giving security, controlling the packet complexity and buffer overflow and also fixing the damages in the existing system.